Phenotype-genotype correlation in haemoglobin H disease in childhood. Issue 6 (December 1983) - Galanello, R; Pirastu, M; Melis, M A; Paglietti, E; Moi, P; Cao, A
Abstract : In this study we used restriction endonuclease mapping to characterise the molecular defect responsible for haemoglobin H disease in 14 Sardinian children. The resulting genotypes were then correlated with the respective clinical and haematological phenotypes. We found that patients with the combination of non-deletion alpha(+)-thalassaemia [(alpha alpha)th] and deletion alpha(0)-thalassaemia (-Med) have a more severe phenotype than that resulting from the interaction of deletion alpha(0)-thalassaemia (-Med) and alpha(+)-thalassaemia (-alpha) determinants. Clinically, presentation was earlier and with moderate anaemia or haemolytic crisis, enlargement of the liver and spleen, and thalassaemic bone changes. Haematologically, the anaemia was more severe and there were higher bilirubin levels, reticulocyte counts, Hb H levels, and percentage of red blood cells with inclusion bodies. These results suggest that in those Hb H disease patients with the non-deletion [(alpha alpha)th] determinant, two alpha globin genes produce fewer alpha globin chains than a single alpha globin locus.